2021
DOI: 10.18502/kls.v6i1.8622
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Preceptor Role and Student Knowledge with Triage Skills in Emergency Department

Abstract: The Emergency Department is a place for clinical practice students to acquire triage experience. Triage can be carried out well by students who are supported by the supervisor and their own knowledge. The objectives of this study were to examine the relationship between the preceptor role and student knowledge with triage skills in emergency department. The research design was cross-sectional. The sample consisted of 43 nursing students who clinical practice in the emergency department. This study used acciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…This study's results align with research conducted by Widiawati et al (2021), which showed a relationship between the role of supervisors and the triage skills of nursing students in the ER Jambi Provincial Hospital in 2019.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…This study's results align with research conducted by Widiawati et al (2021), which showed a relationship between the role of supervisors and the triage skills of nursing students in the ER Jambi Provincial Hospital in 2019.…”
Section: Resultssupporting
confidence: 89%
“…Knowledge about triage skills is needed for nurses who experience it. However, this is also experienced by students in the professional nursing program, following the results of research by Widiawati et al (2021), where 39.5% of students have low triage skills. A similar picture can also be seen from the research conducted by Harigustian (2021), which showed that 42.9% of students had terrible skills.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations